2017
DOI: 10.1039/c6tb03282f
|View full text |Cite
|
Sign up to set email alerts
|

Redox/pH dual-sensitive hybrid micelles for targeting delivery and overcoming multidrug resistance of cancer

Abstract: A three-step approach was used to enhance anticancer activity via targeted delivery, intracellular drug burst release, and depressed drug efflux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…As shown in Figure 11C, when the concentration of Rh123 was 5, 10 and 20 μg/mL, the mean fluorescence intensity of the MCF-7 cells was 108.5-, 147.8-and 155.9-folds higher than that of MCF-7/ADR cells, respectively, which indicated that MCF-7/ADR cells retained strong MDR properties, while the MCF-7 cells were relatively sensitive. 35 Furthermore, the drug efflux inhibition was evaluated on different NPs using MCF-7/ADR cells. As shown in Figure 11D, the mean fluorescence intensity of Rh123 in the cells treated with taxol did not alter significantly.…”
Section: Inhibition Of P-gp Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure 11C, when the concentration of Rh123 was 5, 10 and 20 μg/mL, the mean fluorescence intensity of the MCF-7 cells was 108.5-, 147.8-and 155.9-folds higher than that of MCF-7/ADR cells, respectively, which indicated that MCF-7/ADR cells retained strong MDR properties, while the MCF-7 cells were relatively sensitive. 35 Furthermore, the drug efflux inhibition was evaluated on different NPs using MCF-7/ADR cells. As shown in Figure 11D, the mean fluorescence intensity of Rh123 in the cells treated with taxol did not alter significantly.…”
Section: Inhibition Of P-gp Analysismentioning
confidence: 99%
“…12,35 The transport activity of P-gp was first studied in MCF-7/ADR and MCF-7 cells via fluorescence spectrophotometer. Briefly, MCF-7/ADR or MCF-7 cells were seeded in 24-well plates at 5×10 4 cells/ well.…”
Section: Rhodamine 123 (Rh123) Efflux Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…In brief, a series of drug-free LC-SA/CS-SA micelle solution with various micelle concentrations from 0.001 to 0.5 mg/ml were prepared, and 1 ml of pyrene-in-acetone solution (6 Â 10 À5 M) was added into the micelle solutions respectively and sonicated for dissolution to obtain the final pyrene concentration of 6 Â 10 À7 M. The pre-prepared solutions were equilibrated overnight at 28 C, and the emission spectra of the solutions from 350 nm to 500 nm were recorded at an excitation wavelength of 337 nm by fluorescence spectrophotometer (RF-5301PC, Shimadzu Corporation, Kyoto, Japan). The CMC value was defined as the crosspoint of the two regression lines based on the intensity ratios of first peak at 373 nm to third peak at 384 nm vs. the concentrations of micelle material (Dong et al, 2017;Yang et al, 2017;Yin et al, 2017).…”
Section: Critical Micelle Concentration (Cmc)mentioning
confidence: 99%
“…However, the therapeutic efficacy of chemotherapy is usually limited by multidrug resistance (MDR), especially in advanced stages of cancer. 3,4 Although the mechanism of MDR is complex, the overexpression of P-glycoprotein (P-gp) encoded by the MDR1 gene in cancer cells has been regarded as the major mechanism of MDR, which is able to pump various chemotherapeutics, such as doxorubicin (DOX) and paclitaxel (PTX), out of the cells, leading to low intracellular concentration of drug to kill the cells.…”
Section: Introductionmentioning
confidence: 99%